Os determinantes do endividamento por meio de empréstimo consignado de educadores e servidores do Poder Judiciário do Executivo Estadual Cearense - Barreira, Natacha Medeiros (2014)
This paper examined the determinants of debt of employees of state of Ceará through payroll loans in payroll from the financial situation of these in April 2012, according to data of the Planning Bureau of Ceará (SEPLAG). Econometric models with qualitative and quantitative variables were estimated to examine two proxies of debt: the first model to idebt variable, determines the percentage of gross salary engaged with loans and financing, and second, to variable imargem, investigates the percentage margin for loans or financing that is committed to contracts of this nature and results obtained with high statistical significance can be inferred that: prosecutors, inactive and female educators commit less your salary with loans. On the other hand, it is noted that employees with longer service and teachers are those with greater involvement of the margin for loans, while prosecutors, professionals Judiciary Power and female inactive have less ability to contract them.